Hubungan Status Gizi dengan Citra Tubuh Remaja Putri di SMKN 1 Palu - Putri Ambar; Adillah Imansari; Lilik Sofiatus Solikhah (Lembaga Pengembangan Kinerja Dosen, 2026)
Nutritional status plays an important role in shaping body image among adolescents, particularly female adolescents who experience rapid physical and psychosocial changes. Adolescents with nutritional problems are more likely to feel dissatisfied withitheiribody shape, whichimay lead to unhealthy behaviors such as strict dieting or excessive eating to gain weight. Thisistudy aimed toianalyze theirelationship betweeninutritional statusiand bodyiimage amongifemale adolescentsiat SMK Negeri 1 Palu. This research employedia quantitativeiapproachiwith aicross-sectionalidesign. Aitotal ofi169 femaleistudentsiwere selected using stratified random sampling. Body image data were collected using the Body Self Relation Questionnaire–Appearance Scale, while nutritional status was assessed using Body Mass Index for Age (BMI-for-Age) and Height for Age (HFA). Data were analyzed using the Spearman Rank correlation test. The results indicated that there was no significant relationship between nutritional status based on BMI-for-Age and body image, with a p-value of 0.329. Similarly, no significant relationship was found between Height-for-Age and body image among female adolescents, with a p-value of 0.892. Most respondents were aged 16–17 years, had a negative body image perception, normal BMI-for-Age nutritional status, and normal Height-for-Age category. These findings suggest that body image among female adolescents is not solely influenced by nutritional status but may also be affected by other psychosocial and environmental factors. Therefore, future research is recommended to apply a cohort study design and explore other determinants of body image, such as social media exposure, peer influence, and infectious diseases, to provide a more comprehensive understanding of factors affecting adolescent body image.